2001
DOI: 10.1111/j.1553-2712.2001.tb01275.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of the Risk of Torsades de Pointes in Patients Treated with Intravenous Racemic Sotalol

Abstract: Abstract. Objective: Intravenous (IV) racemic sotalol is useful for the treatment of multiple tachydysrhythmias. The authors hypothesized that the risk of torsades de pointes (TdP) in patients treated with a single IV infusion of sotalol is lower than the 2-4% risk associated with chronic oral sotalol therapy. Methods: A MEDLINE search under the subject heading ''sotalol'' was made of all publications involving humans written in English or German from 1966 to October 1, 2000. A meta-analysis of all original re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…The general impression has been that rapid IV loading increases the risk for pro-arrhythmic toxicity, and thus, IV sotalol is to be avoided. Data contrary to this widely held belief comes from a large metaanalysis that included 37 published reports with 962 patients receiving IV sotalol [10]. Marill and Runge [10] found that "overall risk of Torsade de Pointes in patients treated with a single infusion of IV sotalol is low (0.1%) compared with that in patients given chronic oral sotalol therapy," lower than the 2-4% pro-arrhythmic incidence seen with oral therapy.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…The general impression has been that rapid IV loading increases the risk for pro-arrhythmic toxicity, and thus, IV sotalol is to be avoided. Data contrary to this widely held belief comes from a large metaanalysis that included 37 published reports with 962 patients receiving IV sotalol [10]. Marill and Runge [10] found that "overall risk of Torsade de Pointes in patients treated with a single infusion of IV sotalol is low (0.1%) compared with that in patients given chronic oral sotalol therapy," lower than the 2-4% pro-arrhythmic incidence seen with oral therapy.…”
mentioning
confidence: 82%
“…Data contrary to this widely held belief comes from a large metaanalysis that included 37 published reports with 962 patients receiving IV sotalol [10]. Marill and Runge [10] found that "overall risk of Torsade de Pointes in patients treated with a single infusion of IV sotalol is low (0.1%) compared with that in patients given chronic oral sotalol therapy," lower than the 2-4% pro-arrhythmic incidence seen with oral therapy. The authors employed a much faster infusion of 1.5 mg/kg, or 100 mg sotalol over 30 min than what is recommended in the IV sotalol product label.…”
mentioning
confidence: 82%
“…This is primarily due to its effect on QTc prolongation. Conversely, in a meta-analysis studying 962 patients receiving IV sotalol, the risk of Torsades de Pointes with IV sotalol was 0.1%, significantly lower than with oral sotalol [14] . Piccini et al did discuss that although the all-cause mortality of patients receiving sotalol was greater compared to patients receiving no antiarrhythmic drug therapy, there was a significantly decreased mortality compared to amiodarone (hazard ratio 0.72, 95% CI: 0.55 -0.91, p = 0.0141) [7] .…”
Section: Discussionmentioning
confidence: 99%
“…The incidence is lower in comparison to amiodarone and similar in groups randomized to lidocaine or sotalol. [1], [17], [20] Bradycardia, AV block and heart failure are also reported, especially in patients with low ejection fraction. Non-cardiac adverse effects from intravenous sotalol include nonspecific gastrointestinal or neurological (headache, dizziness, malaise) complaints but the incidence is significantly lower than amiodarone.…”
Section: Pharmacokinetics Of Intravenous Sotalolmentioning
confidence: 99%
“…Alternative explanations for this low incidence of TdP in this study include administration during tachycardia in the acute setting and resultant shortened QT, possible reverse use-dependence, and heterogeneity in dosing and infusion duration. [17] Hypotension is the most commonly reported side effect after intravenous sotalol, particularly when given in the early post-cardiac surgery setting. It is also of clinical significance in patients with VT with or without concomitant use of lidocaine.…”
Section: Pharmacokinetics Of Intravenous Sotalolmentioning
confidence: 99%